Aglaophamus ornatus Hartman, 1967 (Polychaeta-Nephtyidae) da plataforma continental das Ilhas Kerguelen-região sub Antártica - Reis, Maria Alice de Carvalho (1980)
Using material collected by the Oceanographic Expedition MD04 the Continental Shelf of Kerguelen Islands, Subantarctic Region, we focused the population of Aglaophamus ornatus Hartman, 1967, Polychaeta Nephtyidae. The systematic problems presented by a certain number of species and the distribution of the species of the genus Aglaophamus are brought up and discussed as well as the dominance and the density of the different zoological groups found to be present, in relation to certain systematic and biogeographic aspects.